1988
DOI: 10.1111/j.1526-4610.1988.hed2802124.x
|View full text |Cite
|
Sign up to set email alerts
|

Common Migraine: Criteria for Diagnosis

Abstract: SYNOPSIS Current definitions of common migraine are not specific and new criteria are needed. Our concept of common migraine was supported by comparing the features of 100 consecutive patients we diagnosed as common migraine, with past series. The features of our patients with common migraine were then compared with 100 cases of chronic daily headache, the only form of “tension headache” that can unequivocally be differentiated from migraine. The features that occurred significantly (P<0.001) more often in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…A previous study validated the IH S criteria on a clinical sample of 81 headache sufferers, but its aim was to compare diagnosis using IHS criteria and previous N IH criteria [10]. The authors found a good correlation between the two classifications [11]; the IH S criteria can not, however, be considered as the reference for the diagnosis of migraine [12,13].…”
Section: Discussionmentioning
confidence: 96%
“…A previous study validated the IH S criteria on a clinical sample of 81 headache sufferers, but its aim was to compare diagnosis using IHS criteria and previous N IH criteria [10]. The authors found a good correlation between the two classifications [11]; the IH S criteria can not, however, be considered as the reference for the diagnosis of migraine [12,13].…”
Section: Discussionmentioning
confidence: 96%
“…This abnormal power spectrum may provide an additional criteria for the diagnosis of migraine. 20,22 Migraine patients treated with propranolol (group A) present a clear reduction to normal level, in the power of HR fluctuations in the frequency range below 0.1 Hz. 20 This low frequency range is mediated by combined vagal and sympathetic nervous control.…”
Section: Discussionmentioning
confidence: 99%
“…In establishing the diagnosis, criteria based on the Ad-Hoc Committee (1962) were utilized. 21,22 All patients had their ECG recorded with the same Holter recorder. All of them were admitted to the hospital 24h prior to the Holter study, which took place during a headache free interval.…”
Section: Subjectsmentioning
confidence: 99%
“…19,20 No cluster headache or mixed vascular headache patients were included. All patients suffered from migraine, diagnosed according to the Ad-Hoc Committee on Classification of Headache.…”
Section: Subjectsmentioning
confidence: 99%